Professional Work Reconfigured: Emerging Skills and Competences for Leaders in the Digital Age - Laura BENCHEA; Anca Gabriela ILIE (Communications of International Proceedings, 2021)
The rapid advances of Information and Communication Technologies (ICT) with increasingly capable systems, sophisticated machines and unprecedented interconnectedness are at the core of the current social, economic and business developments. Inquiries about the pace of transformations and the impact of new technologies on the future of professions have become major themes in the academic, public and business discourses. The new social and economic conditions reconfigure new forms of leadership which imply new skills, competences, attitudes and knowledge considered to be vital for successful outcomes in this competitive business environment. Therefore, the purpose of this paper is to capture the major characteristics and trends of the professional restructuring imposed by the digital transformations, with a focus on leadership, and the skills and competences needed to be acquired in order to effectively respond to the new challenges imposed by the technological disruption.
Keywords: Leadership; Digital Age; Technology; Agile Leaders.